2016
DOI: 10.7863/ultra.15.03003
|View full text |Cite
|
Sign up to set email alerts
|

Customized Fetal Growth Charts for Parents' Characteristics, Race, and Parity by Quantile Regression Analysis

Abstract: In this study we constructed customized biometric growth charts using quantile regression in a large cohort of low-risk pregnancies. These charts offer the advantage of defining individualized normal ranges of fetal biometric parameters at each specific percentile corrected for parental height and weight, parity, and race. This study supports the importance of including these variables in routine sonographic screening for fetal growth abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…24 Similar associations between maternal-child BMI and paternal-child BMI at 3 years have been reported; 25 and as others, 26 they questioned the contribution by the intrauterine environment and suggested that prevention of childhood adiposity will benefit more from postnatal than prenatal intervention. 25 The role of ethnicity is not clear, as a small effect on fetal biometry is reported in some studies, 20,21 the large Intergrowth-21st study found no effect of ethnicity after adjustment for socioeconomic confounders, 27 which supports the Barker hypothesis. 1,2 There is some disagreement about the mechanism behind maternal constraint and possible explanations that have been suggested are: (1) maternal regulation of fetal nutrition, (2) maternal hormone regulation, or (3) cytoplasmic inheritance.…”
Section: 339mentioning
confidence: 86%
See 1 more Smart Citation
“…24 Similar associations between maternal-child BMI and paternal-child BMI at 3 years have been reported; 25 and as others, 26 they questioned the contribution by the intrauterine environment and suggested that prevention of childhood adiposity will benefit more from postnatal than prenatal intervention. 25 The role of ethnicity is not clear, as a small effect on fetal biometry is reported in some studies, 20,21 the large Intergrowth-21st study found no effect of ethnicity after adjustment for socioeconomic confounders, 27 which supports the Barker hypothesis. 1,2 There is some disagreement about the mechanism behind maternal constraint and possible explanations that have been suggested are: (1) maternal regulation of fetal nutrition, (2) maternal hormone regulation, or (3) cytoplasmic inheritance.…”
Section: 339mentioning
confidence: 86%
“…[20][21][22][23][24][25] In a retrospective multicenter study, paternal and maternal height and maternal weight were associated with fetal HC, AC and FL. 20,21 In the Intergrowth-21st study, fathers of infants born large-for-gestational-age were taller and heavier but they had similar BMI. 22 Paternal height predicted large-for-gestational-age in boys and girls, but paternal BMI was not associated with greater odds ratio…”
Section: Discussionmentioning
confidence: 99%
“…Although the birth weight distribution of our study population of 3,440 newborns was well-matched to the distribution of birth weight of newborns included in the INTERGROWTH-21 st project, this was not the case for two of the four ultrasound parameters (biparietal diameter and femur length). The most likely reasons for discrepancies are differences in the measurement techniques between the two studies (for BPD) and racial differences for femur length [15,32]. Therefore, in this study, we have used INTERGROWTH-21 st standards to classify neonates as SGA and LGA but relied on locally derived reference ranges for fetal biometry.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to references, fetal growth standards are developed under optimal conditions, excluding pathology, and are intended for general use. Customized fetal biometry standards accounting for individual maternal characteristics have been created, [97][98][99] but may have limited applicability in low-resource settings. Recent longitudinal studies in healthy pregnancies have been undertaken by the NICHD in the United States, 74 WHO, 75 and INTERGROWTH-21st, 100 with the aim of developing population fetal growth standards for international use.…”
Section: Research Prioritiesmentioning
confidence: 99%